2019
DOI: 10.1021/acsomega.9b03494
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Surface Modification and Immobilization Method of Anti-CD25 Antibody on Nonwoven Fabric Filter Removing Regulatory T Cells Selectively

Abstract: Anti-CD25 antibodies were immobilized on polypropylene (PP) nonwoven fabrics to specifically remove mouse regulatory T cells (Tregs) from mouse spleen cells. PP fibers were coated with peptide nanosheets, which were prepared by self-assembling of a mixture of X-poly­(sarcosine)-b-(l-Leu-Aib)6 (X: glycolic acid or a phenylboronic acid) and Y-poly­(sarcosine)-b-(d-Leu-Aib)6 (Y: glycolic acid or diazirine derivative). Anti-CD25 antibodies were immobilized by covalent linking between the sugar moiety of the antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…57,58 membrane have higher LPS adsorption capacity than AN69 membrane, which is related to the high amount of cationic functional groups of PEI. 78,79 In addition, more advanced peptide nanosheets coating on polypropylene (PP) nonwoven fabrics was proposed by Uji et al 80 These peptide nanosheets have two faces, one for phenylboronic acid to connect to site-oriented antibodies to remove regulatory T cells specifically, and the other for photoactivable radical generator to react with PP fiber to improve the compatibility of PP fiber. This method established a strategy of highly biocompatible surface coating on pristine hemoperfusion materials, which pioneered the research of peptide and protein coating materials.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…57,58 membrane have higher LPS adsorption capacity than AN69 membrane, which is related to the high amount of cationic functional groups of PEI. 78,79 In addition, more advanced peptide nanosheets coating on polypropylene (PP) nonwoven fabrics was proposed by Uji et al 80 These peptide nanosheets have two faces, one for phenylboronic acid to connect to site-oriented antibodies to remove regulatory T cells specifically, and the other for photoactivable radical generator to react with PP fiber to improve the compatibility of PP fiber. This method established a strategy of highly biocompatible surface coating on pristine hemoperfusion materials, which pioneered the research of peptide and protein coating materials.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Thus, their secondary structures and physicochemical properties are strongly determined by their sidechains, which allows modulation through side chain design. For example, peptoids comprising C1 or C2 alkyl side chains, i. e., poly( N‐ methylglycine) or poly( N ‐ethylglycine), are hydrophilic, whereas peptoids containing four or more carbons are hydrophobic, and poly( N ‐C3 glycines) exhibit a thermoresponsive behavior [1–6] . Secondary structures are also affected by side chains, with peptoids adopting a random coil structure in the presence of small side chains and assuming a helical conformation in the presence of bulky and chiral side chains [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have shown that peptoids have low cytotoxicity [20–25] . Taking the advantages of these advantages, peptoids are applied to non‐fouling coatings, [6,26,27] protein‐purification components, [28–31] antibacterial agents, [32–39] and therapeutic agents [36,40–45] …”
Section: Introductionmentioning
confidence: 99%
“…Several treatments that inhibit immunosuppressive signal transduction by immune checkpoint inhibitors (e.g., anti-CTLA-4 and anti-programmed death-1 antibodies) and depletion of Tregs by administration of anti-C-C motif chemokine receptor 4 antibodies have been proposed as Treg-related cancer immunotherapies [8,9]. The development of selective Treg removal methods is also proposed [10,11]. Although the efficacies of these treatments have been demonstrated, treatment with immune checkpoint inhibitors can induce serious side effects owing to activation of T cells [12].…”
Section: Introductionmentioning
confidence: 99%